Conceptions regarding upbringing: the thoughts of parents - Infante Blanco, Alejandra (2016)
Being the family one of the main institutions of human development, it becomes one of the responsible pillars upon which the personal and social well-being is sustained, in addition to constituting the space where a particular vision of the world is built. This makes the study of parent’s thoughts relevant (expressed through beliefs), who become the main actors of upbringing and therefore of the welfare and family development. The present work has as its aim to assess the concepts that parents maintain about parenting. Participants included 40 families who answered a designated questionnaire of parental models (Martinez, Salazar & Infante, 2013), and a semi-structured interview which inquired about the family dynamics and child-rearing practices. The results indicate that the parental model translates into a negotiated upbringing pattern; a link of closeattachment and a pattern of success promoter. In the interview analysis they found four categories that show the aspects of upbringing that participants perceive as easy and difficult; the personal perceptions on the role of parents being carried out, and the most common challenges facing families today. It is concluded that parental thoughts regarding upbringing is produced from their knowledge, beliefs and attitudes clearly influenced by the nearby social context, the dominant culture, and the inherited culture on the rooted family in the previous upbringing experiences. DOI: https://doi.org/10.24265/liberabit.2016.v22n1.03